PENGARUH KONSENTRASI SUKROSA TERHADAP KARAKTERISTIK YOGHURT DARI SUSU KULIT PISANG KEPOK (Musa paradisiaca formatypica) DAN KACANG HIJAU (Phaseolus radiatus L.) - J. Christy Dante, Laura; Suter, I Ketut; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA, 2017)
This research was conducted to determine the best sucrose concentration of the best yoghurt characteristic that was made by banana peeled and mung bean milk. The research was using complete randomized block design (CRBD) with sucrose concentration as the treatment which consists of seven levels, there were 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, and 15%. The parameters observed were total sugar, lactic acid bacteria population, lactic acid (titrable acidity), pH, and sensory characteristics, such as color, flavor, taste, texture, consistency, and overall acceptance. The results showed that the characteristics of banana peeled and mung bean yogurt was affected by sucrose concentration. The best treatment was 7.5% sucrose concentration which had total sugars at 1,71%, lactic acid bacteria populations at 7.3x10 9 CFU/ml, lactic acid acidity at 0.89%, pH at 3.56, color were slightly like, the flavor were slightly like, the taste were slightly sour and slightly like, the texture were thick, the consistency were homogeny, and overall acceptance were like.
Keywords: Yogurt, banana peeled, mung bean, sucrose